A QTL on chromosome 3q23 influences processing speed in humans. (16th November 2018) - Knowles, Emma E. M.; Mathias, Samuel R.; Mollon, Josephine; Rodrigue, Amanda; Koenis, Marinka M. G.; Dyer, Thomas D.; Goring, Harald H. H.; Curran, Joanne E.; Olvera, Rene L.; Duggirala, Ravi; Almasy, Laura; Blangero, John; et al.
Abstract : Processing speed is a psychological construct that refers to the speed with which an individual can perform any cognitive operation. Processing speed correlates strongly with general cognitive ability, declines sharply with age and is impaired across a number of neurological and psychiatric disorders. Thus, identifying genes that influence processing speed will likely improve understanding of the genetics of intelligence, biological aging and the etiologies of numerous disorders. Previous genetics studies of processing speed have relied on simple phenotypes (eg, mean reaction time) derived from single tasks. This strategy assumes, erroneously, that processing speed is a unitary construct. In the present study, we aimed to characterize the genetic architecture of processing speed by using a multidimensional model applied to a battery of cognitive tasks. Linkage and QTL‐specific association analyses were performed on the factors from this model. The randomly ascertained sample comprised 1291 Mexican‐American individuals from extended pedigrees. We found that performance on all three distinct processing‐speed factors ( Psychomotor Speed ; Sequencing and Shifting and Verbal Fluency ) were moderately and significantly heritable. We identified a genome‐wide significant quantitative trait locus (QTL) on chromosome 3q23 for Psychomotor Speed (LOD = 4.83). Within this locus, we identified a plausible and interesting candidate gene for Psychomotor Speed ( Z = 2.90, P = 1.86 × 10 −03 ). Abstract : A novel locus for processing‐speed ability identified in humans on chromosome 3q23.